An elaboration of technology for bell pepper breeding for the regions with reduced heating supply - M.I. Mamedov; O.N. Pyshnaya; I.A. Lyengalycheva (Овощи России, 2008)
The technology for bell pepper breeding program has been elaborated for the regions with reduced heating supply. The selected cold resistance forms of bell pepper served as the basis for modeling of cold stresses and pathogen infections being studied at different stages of plant growing. In conditions of protected cultivation, there are cultivars Slastena, Kazachok, pamiyti Zhegalova and some breeding forms were selected. These cultivars can also be grown in open field conditions in Nonchernozem zone.